Protocol for implementation of intraoperative adverse event recording during WHO checklist sign-out - Guy Haller; Lauren Clack; Christian Schindler; Luzius A Steiner; Salome Dell-Kuster; Dieter Hahnloser; Jörn-Markus Gass; Christoph S Burkhart; Andreas P Vogt; Katrin Burri-Winkler; Anne C Auderset; Valentin Neuhaus; et al. (BMJ Open Quality)
Introduction & aim Intraoperative adverse events (iAEs) increase postoperative complications, which are devastating to patients and costly to healthcare systems. To optimise patient outcomes, the WHO Surgical Safety Checklist (WHO SSC) was introduced in 2008, but adherence, especially to its third part (sign-out), is low, and iAEs are currently not routinely assessed. This gap between evidence supporting the use of the WHO SSC, current inconsistent sign-out practice and the lack of standardised reporting of iAEs warrants applying an implementation science approach. Hence, this project aims to simultaneously evaluate the effectiveness and implementation of the sign-out, including systematic recording and discussion of iAEs during the sign-out.Methods & analysis Using a hybrid effectiveness-implementation approach, this prospective before-and-after-cohort project includes five surgical disciplines within nine Swiss hospitals. Following an extensive context analysis, this project is set up in three phases: (1) recruitment of 40 patients per surgical discipline and site (approx. 900 in total) for baseline assessment; (2) implementation based on a multifaceted, tailored implementation strategy (including formation of implementation teams, comprehensive education of healthcare professionals, top-down leadership, regular feedback rounds and tailoring implementation to local needs); and (3) recruitment of 40 patients per discipline to assess the changes after implementation (approx. 900). Implementation (eg, checklist fidelity composed of completion and quality) and effectiveness outcomes (ie, clinical patient outcomes) will be analysed using a mixed regression model.Discussion & conclusion By enhancing adherence to the WHO SSC sign-out, including standardised reporting of iAEs, we expect to further improve perioperative patient outcomes. Based on the context analysis, we will provide a widely applicable implementation plan to support and sustain the required behavioural change, which will support roll-out in further hospitals. Meanwhile, clinical and implementation science expertise is meeting the challenges of the complex environment of perioperative care.